Fabrication of Ordered, Large Scale, Horizontally‐Aligned Si Nanowire Arrays Based on an In Situ Hard Mask Block Copolymer Approach. (26th November 2013) - Ghoshal, Tandra; Senthamaraikannan, Ramsankar; Shaw, Matthew T.; Holmes, Justin D.; Morris, Michael A.
<x xml:space="preserve">Abstract</x> A simple technique is demonstrated to fabricate horizontal, uniform, and hexagonally arranged Sinanowire arrays with controlled orientation and density at spatially well defined locations on a substrate based on an in situ hard‐mask pattern‐formation approach by microphase‐separated block‐copolymer thin films. The technique may have significant application in the manufacture of transistor circuitry. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>